DAYA TARIK FACEBOOK SEBAGAI MEDIA KOMUNIKASI ALTERNATIF - Marlina Marlina (Program Pascasarjana Universitas Islam Negeri Sumatera utara, 2016)
Communication is a necessity that can not be avoided by human being, since communication is also a primary needs for every social creatures. Nowadays, we find on each social status; regardless of social status, education level and occupation then communication takes place on the virtual world, with social media facilities that are very diverse, therefore the communications made by each person more easily and quickly. They will find new friends there, old friends who had not seen a long time, and others. Observing every detail of the text that used by social media user when interacting with friends on